Decreased ability in the segregation of dynamically changing vowel-analog streams: a factor in the age-related cocktail-party deficit? - Divenyi, Pierre (Frontiers in Neuroscience, 2014)
Pairs of harmonic complexes with different fundamental frequencies f0 (105 and 189 Hz or 105 and 136 Hz) but identical bandwidth (0.25-3 kHz) were band-pass filtered using a filter having an identical center frequency of 1 kHz. The filter’s center frequency was modulated using a triangular wave having a 5-Hz modulation frequency fmod to obtain a pair of vowel-analog waveforms with dynamically varying single-formant transitions. The target signal S contained a single modulation cycle starting either at a phase of - π /2 (up-down) or π /2 (down-up), whereas the longer distracter N contained several cycles of the modulating triangular wave starting at a random phase. The level at which the target formant’s modulating phase could be correctly identified was adaptively determined for several distracter levels and several extents of frequency swing (10-55%) in a group of experienced normal-hearing young and a group of experienced elderly individuals with hearing loss not exceeding one considered moderate. The most important result was that, for the two f0 differences, all distracter levels, and all frequency swing extents tested, elderly listeners needed about 20 dB larger S/N ratios than the young. Results also indicate that identification thresholds of both the elderly and the young listeners are between 4 and 12 dB higher than similarly determined detection thresholds and that, contrary to detection, identification is not a linear function of distracter level. Since formant transitions represent potent cues for speech intelligibility, the large S/N ratios required by the elderly for correct discrimination of single-formant transition dynamics may at least partially explain the well-documented intelligibility loss of speech in babble noise by the elderly. [Work supported by grants from the National Institute on Aging and the Veterans Affairs Medical Research.]